Green Public Procurement Sebagai Salah Satu Implementasi SDGs Sektor Publik Kota Samarinda - Dian Irma Aprianti; Sugeng Chairuddin (Badan Pengembangan Sumber Daya Manusia Provinsi Kalimantan Timur, 2024)
Environmentally friendly public procurement (GPP) has been widely adopted as a public administration tool to achieve sustainability outcomes. However, there is a lack of understanding regarding the determinants of Green Public Procurement adoption, namely the characteristics of the contracting authority. This research aims to analyze the extent to which Green Public Procurement is implemented in Public Sector services in Samarinda, where this is one of the absorptions of the Government’s Long Term Program, namely Sustainable Development (SDGs). This analysis uses descriptive qualitative methods with observation, interviews and empirical review methods. The results of the research show that there are challenges in the implementation of Environmentally Friendly Goods and Services Procurement, especially in regulations that have not been updated, Human Resources are still limited, Work Flow is still hampered, and Inadequate Network Devices. There is still a need for service standards and standards for the use of equipment and work equipment that support the procurement of environmentally friendly goods and services. However, basically the Implementation of Procurement of Environmentally Friendly Goods and Services in the Samarinda City Government Sector has been implemented correctly, although in several cases there are still things that need to be completed.